2017
DOI: 10.1186/s12888-017-1330-2
|View full text |Cite
|
Sign up to set email alerts
|

Imagery rescripting and eye movement desensitisation and reprocessing for treatment of adults with childhood trauma-related post-traumatic stress disorder: IREM study design

Abstract: BackgroundPost-traumatic stress disorder (PTSD) that originates from childhood trauma experiences can develop into a chronic condition that has lasting effects on an individual’s functioning and quality of life. While there are evidence-based guidelines for treating adult onset PTSD, treatments for adults with childhood trauma-related PTSD (Ch-PTSD) are varied and subject to ongoing debate. This study will test the effectiveness of two trauma-focused treatments, imagery rescripting (ImRs) and eye movement dese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 54 publications
0
26
0
3
Order By: Relevance
“…One approach to treating CT-associated PTSD symptoms has been trauma-focused cognitive behavioral therapy (CBT), but high drop-out rates have been reported and some have suggested that prolonged exposure and a focus on trauma reprocessing is not appropriate (McDonagh et al, 2005 ; Cloitre et al, 2011 ; Boterhoven de Haan et al, 2017 ). This has led to exploration of alternative trauma-focused approaches for the treatment of CT.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to treating CT-associated PTSD symptoms has been trauma-focused cognitive behavioral therapy (CBT), but high drop-out rates have been reported and some have suggested that prolonged exposure and a focus on trauma reprocessing is not appropriate (McDonagh et al, 2005 ; Cloitre et al, 2011 ; Boterhoven de Haan et al, 2017 ). This has led to exploration of alternative trauma-focused approaches for the treatment of CT.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are no notable differences in effectiveness between IR and ET, several elements are proposed in order to make IR a therapeutic option of relevance for certain cases of PTSD. On the one hand, IR can break the patterns of victimization, impotence, and passivity of people who have suffered a trauma ; on the other hand, IR would be a treatment of choice because it is considered less aversive, invasive, and emotionally activating for the therapist and patients (e.g., de Haan et al, 2017) and the therapeutic alliance is less compromised than with the ET (Hoffart et al, 2013). In addition, according to Arntz et al (2012), IR may be especially indicated for patients resistant to cognitive behavioral therapy in whom cognitive restructuring or rational debate do not work.…”
Section: Resultsmentioning
confidence: 99%
“…No obstante, hacen falta más trabajos con buenos diseños de investigación para poder emitir conclusiones robustas acerca de las diferencias entre la RI y la exposición, así como para conocer sus mecanismos de acción. De hecho, hay autores que rebaten con argumentos empíricos la idea clásica acerca de que las técnicas de exposición son útiles únicamente para el abordaje del miedo y no para traumas en los que predominan emociones como la culpa, la ira o la vergüenza (de Haan et al, 2017).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Therapists can reduce time pressure by starting promptly with the IR or by scheduling longer sessions. For example, for treatments for PTSD with IR, the session length is up to 90 min to allow for enough time for emotional processing and debriefing ( 26 ). Also, therapists can allow for enough time for the patient to process each step during the IR and leave enough time for debriefing and stabilization after the IR.…”
Section: Clinical and Research Implications Of The Findingsmentioning
confidence: 99%